1993
DOI: 10.1364/ao.32.006975
|View full text |Cite
|
Sign up to set email alerts
|

Silicide layer growth rates in Mo/Si multilayers

Abstract: The thermal stability of sputter-deposited Mo/Si multilayers was investigated by annealing studies at relatively low temperatures (˜ 250-350 °C) for various times (0.5-3000 h). Two distinct stages of thermally activated Mo/Si interlayer growth were found: a primary surge, followed by a (slower) secondary steady-state growth in which the interdiffusion coefficient is constant. The interdiffusion coefficients for the interlayer formed by deposition of Mo-on-Si are higher than those of the interlayer formed by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
3
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 13 publications
4
67
3
2
Order By: Relevance
“…In addition, the interdiffusion and formation of silicide occur when the energy is higher than the activation energy, about 2 eV. The formation temperature of silicide is above 200°C and the formation temperature of crystalline MoSi 2 even higher up to 525°C, suggesting the long-term thermal stability at low temperatures (below 100°C) is consistent with our experiment results [13][14][15][16]. The maximum temperature of multilayer mirrors in the solar telescope during future missions will be approximately 100°C, so that the thermal stability of Mo/Si multilayer could well meet the requirements of solar observation missions in future.…”
Section: Thermal Stabilitysupporting
confidence: 90%
“…In addition, the interdiffusion and formation of silicide occur when the energy is higher than the activation energy, about 2 eV. The formation temperature of silicide is above 200°C and the formation temperature of crystalline MoSi 2 even higher up to 525°C, suggesting the long-term thermal stability at low temperatures (below 100°C) is consistent with our experiment results [13][14][15][16]. The maximum temperature of multilayer mirrors in the solar telescope during future missions will be approximately 100°C, so that the thermal stability of Mo/Si multilayer could well meet the requirements of solar observation missions in future.…”
Section: Thermal Stabilitysupporting
confidence: 90%
“…Optical properties of X-ray multilayers are defined by the real structure of a multilayer coating, featuring constant multilayer periodicity H = t Mo + t Si and thickness ratio of components Γ = t Mo /H across the whole multilayer stack, values of interface roughness and density of each layer, and the presence of interlayers at interfaces. In the current decade, the scientific world has made progress in understanding the nature of the real structure of multilayer periodical Mo/Si compositions [1][2][3][4][5][6][7][8][9][10]. It was found that besides the parameters mentioned above, a significant effect on optical properties of X-ray multilayers is given by internal macroscopic stresses that occur during the preparation of multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…An amorphous to crystalline transition occurs in the Mo layer for a thickness around 2 nm. This transition results in a significant decrease in the silicide layer for the Si on Mo interface [4]. In our modeling it is assumed that the interface layers are MoSi 2 .…”
Section: Silicidementioning
confidence: 99%